2023
DOI: 10.1186/s12967-023-04345-7
|View full text |Cite
|
Sign up to set email alerts
|

An Fgr kinase inhibitor attenuates sepsis-associated encephalopathy by ameliorating mitochondrial dysfunction, oxidative stress, and neuroinflammation via the SIRT1/PGC-1α signaling pathway

Abstract: Background Sepsis-associated encephalopathy (SAE) is characterized by diffuse brain dysfunction, long-term cognitive impairment, and increased morbidity and mortality. The current treatment for SAE is mainly symptomatic; the lack of specific treatment options and a poor understanding of the underlying mechanism of disease are responsible for poor patient outcomes. Fgr is a member of the Src family of tyrosine kinases and is involved in the innate immune response, hematologic cancer, diet-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…The SIRT1/PGC1α signaling pathway is a pivotal molecular cascade intricately involved in governing diverse cellular processes including energy metabolism, cellular oxidative stress responses, and inflammation [ 48 50 ]. At its core, SIRT1, a NAD + -dependent deacetylase belonging to the sirtuin family, exerts its influence by removing acetyl groups from specific target proteins, thereby regulating their activity [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The SIRT1/PGC1α signaling pathway is a pivotal molecular cascade intricately involved in governing diverse cellular processes including energy metabolism, cellular oxidative stress responses, and inflammation [ 48 50 ]. At its core, SIRT1, a NAD + -dependent deacetylase belonging to the sirtuin family, exerts its influence by removing acetyl groups from specific target proteins, thereby regulating their activity [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The maintenance of a healthy mitochondrial network, fundamental to support cell energy demand, is strictly dependent on mitochondrial fission and fusion dynamics, a process regulating changes in mitochondrial size and shape, growth and redistribution, as well as intervening in mitochondrial cristae remodeling [ 53 ]. Such a “mitochondrial quality control” system has been found frequently deregulated in pathological conditions, including cardiovascular diseases [ 8 , 54 ], non-alcoholic fatty liver disease [ 55 ], acute kidney injury [ 56 ], neurodegenerative disorders [ 57 , 58 ], diabetes mellitus [ 59 ], skeletal muscle atrophy [ 60 ], and many others.…”
Section: Discussionmentioning
confidence: 99%
“…Liu and collaborators have observed that in cerebral tissue of septic mice treated with cecal ligation and puncture (CLP), the activation of the SIRT1/PGC-1α pathway not only reversed mitochondrial structural damage but also mitigated the elevation of ROS and malondialdehyde (MDA) levels, and the restoration of SOD levels has been achieved. This also significantly improved the activity of mitochondrial respiratory chain complexes, markedly alleviating sepsis-associated encephalopathy ( 114 ).…”
Section: Sirts and Pathophysiology Of Sepsismentioning
confidence: 99%